Karir Di Kedokteran Forensik: Perspektif Hari Ini Dan Masa Depan - Noverika Windasari; Citra Manela; Sani Tanzilah; Putri Dianita Ika Meilia (Majalah Kedokteran Indonesia, 2022)
Introduction: The lack of experts in forensic medicine will become a serious problem globally in the future. In Indonesia, the unique position of forensic medicine at the intersection between medicine and law itself means that the role of forensic doctors can still expand widely. The future development of forensic medicine in Indonesia is determined mainly by forensic doctors and prospective forensic doctors themselves. Therefore, this study aims to determine the motivation of doctors in choosing the specialty of forensic medicine and their views on work as forensic doctors. Methods: This is a cross-sectional descriptive observational research using mixed methods, with forensic doctors and residents as respondents. Result: The results show that 17.8% chose forensic medicine because of their interests and 11.1% because they considered forensic medicine to be a challenging specialty. The absence of scholarships, the lack of institutional and family support, the lack of number and variety of cases in various educational centers, and the limited supporting facilities and financing of forensic medical services are the main obstacles for forensic doctors. Conclusion: Regeneration is needed to meet the need of forensic doctors in various regions in Indonesia by spreading information about the importance of forensic medicine. Good coordination between forensic experts, the Indonesian Forensic Doctors Association (PDFI), other professional organizations, and relevant stakeholders is needed to overcome various obstacles and ensure the growth of forensic medicine in Indonesia.